Intervenção em equidade de gênero: Teste inicial na promoção de cooperação, aspiração à carreira e conhecimento das desigualdades de gênero - Frutuoso, Deniel Gomes (2024)
Proposals for gender equity at work focused on the individual have been questioned, opening space for a new perspective that seeks to produce structural changes in organizations. In this scenario, it is desirable to carry out theoretical-practical studies capable of changing beliefs about gender differences between women and men at work. Therefore, the objective of this study was to build an awareness intervention about gender inequalities at work and evaluate its impact on gender equity knowledge, career aspirations and willingness to cooperate with women in a technology company. The workshop was built based on a needs assessment of the participating company and based on theoretical career and gender references. The samples were composed of intervention (n=21) and control (n=114) groups, with a predominance of women and higher education graduates in both groups. Data were collected using psychometric scales and a sociodemographic questionnaire. Descriptive and inferential statistics were used, such as mean, independent t-test and paired samples, normality test, resampling and post-hoc. The results did not support the effectiveness of the intervention to promote the study variables. Based on these findings, guidelines for bias mitigation interventions, promoting diversity in organizations and building conducive environments for women's cooperation and career aspirations are discussed.